Dynamic effects of China’s national volume-based procurement on generic drug consistency evaluation: An interrupted time series analysis - Xianli Ge; Xiaodong Liu; Weiyu Tian; Jing Peng; Mingyue Zhao; Yu Fang (PLoS ONE, 2026)
Objectives China’s national volume-based procurement (NVBP) policy uniquely requires the generic drug consistency evaluation (GCE) for generic drugs on the purchase list. It employs large-scale centralized procurement to lower the prices of qualified generic drugs and encourages manufacturers to get GCE certification for their generic drugs. Although it is a fundamental part of the NVBP system, research on the impact of NVBP on manufacturers has only recently emerged and is still not comprehensive enough. This study is the first to systematically evaluate the dynamic effects of the NVBP policy on the quantity of GCE-certified generic drugs and uncover their relationship in terms of both time and quantity. Study design Interrupted time series analysis(ITSA). Methods The NVBP lists were published by the National Healthcare Security Administration (NHSA). The information of GCE-certified generic drugs was obtained from the databases of the National Medical Products Administration (NMPA) and the Center for Drug Evaluation (CDE). Generic drugs were divided into four categories: all GCE-certified generics; GCE-certified generics of NVBP-listed drugs (NVBP-GCE generics); GCE-certified generics of non-NVBP drugs (non-NVBP GCE generics); and GCE-certified generics from each individual NVBP list. Results Overall, the 2018 NVBP intervention resulted in a monthly increase of 2.876 in generics certified by GCE (95% CI: 1.311–4.317). In contrast, the 2016 policy showed no statistical significance. Both NVBP-GCE and non-NVBP GCE generics experienced significant increases, with NVBP-GCE showing a more rapid initial rise. In the analysis of 8 NVBP batches, the 2016 intervention had no significant statistical impact on either the immediate or long – term effects. Conversely, the 2018 intervention significantly increased the quantity of GCE – certified generics in the short term and widened the gap between NVBP – GCE generics and non – NVBP GCE generics. Nevertheless, this effect gradually diminished over time. The quantity of NVBP – GCE generics reached its peak before or at the release of each NVBP list, while non – NVBP GCE generics continued to grow. Conclusion The NVBP policy has resulted in a substantial increase in the quantity of GCE – certified generic drugs. From a comprehensive perspective, the growth rates of NVBP-GCE generics and non-NVBP GCE generics were comparable. The maximum number of GCE – certified generic drugs was witnessed either prior to or simultaneously with the release of each round of NVBP procurement documents. After the publication of each NVBP announcement, the number of GCE – certified generics on that particular procurement list started to decrease, whereas the number of non – NVBP GCE generics continued to increase steadily until April 2024.